PWE-133 Follow-up management of coeliac disease – who, when, where and what?. (17th June 2017) - Pritchard, L; Bebb, JR; Abdelrahim, M; Waters, C; Murray, IA; Lewis, SJ
Abstract : Introduction: Annual review of coeliac patients to monitor clinical status, dietary adherence and manage further complications is advised by NICE 1 . We describe adherence to guidelines for patients from adjacent Trusts, one managing patients mainly through a specialist nurse led telephone clinic (NLTC) (Royal Cornwall hospital), the other returning patients to primary care (Plymouth hospitals). Method: Postal questionnaire of 835 patients with coeliac disease (CD), diagnosed via positive serology and duodenal biopsy, who attended secondary care services at one of two hospitals between 2006 and 2014. Patients were diagnosed at least 24 months earlier. Patients reported annual reviews (AR) over the last 3 years, clinical history (weight, height, symptoms, dietary review), investigations (blood tests, vaccinations, DXA referral), prescription of calcium/vitamin D supplements, bisphosphonates and ongoing conditions related to CD i.e. anaemia and osteoporosis. Results: 516 patients (61.8%) responded. Comparing follow-up between sites, those at Cornwall (84%) were more likely to have AR compared to those at Plymouth (28%) (p<0.0001). In Cornwall, 89% of patients were followed up by NLTC, 2% by GP and 7% by a doctor in outpatients. This is in contrast to Plymouth where all reviews were by GPs. Those under regular review (89% NLTC) had more follow-up tests than those under GPs (Table 1). More patients under GP follow-up had prescriptions for calcium/vitamin D supplements and bisphosphonates. Conclusion: There is wide variation in local practices of coeliac follow-up and many patients do not get an AR. Only one-third of patients who were discharged back to their GP in Plymouth had an AR compared to 84% in Cornwall where many patients had NLTC review. Patients having AR were more likely to have follow-up tests and investigations in line with NICE guidance and this may result in better outcomes for patients. Future research is required to investigate the optimal way of monitoring patients with CD, the value of self-monitoring and the effect of follow-up on complications associated with CD. Reference: Coeliac disease: recognition, assessment, and management (2015) NICE guidelines NG20. Disclosure of Interest: None Declared